Numerical prediction of creep rupture life of ex-service and as-received grade 91 steel at 873 K - Ferdous, I. U.; Nasrul Azuan, Alang; Juliawati, Alias; S., Mohd Nadzir (Universiti Malaysia Pahang, 2021)
Infallible creep rupture life prediction of high temperature steel needs long hours of robust testing over a domain of stress and temperature. A substantial amount of effort has been made to develop alternative methods to reduce the time and cost of testing. This study presents a finite element analysis coupled with a ductility based damage model to predict creep rupture time under the influence of multiaxial stress state of ex-service and as-received Grade 91 steel at 873 K. Three notched bar samples with different acuity ratios of 2.28, 3.0 and 4.56 are modelled in commercial Finite Element (FE) software, ABAQUS v6.14 in order to induce different stress state levels at notch throat area and investigate its effect on rupture time. The strain-based ductility exhaustion damage approach is employed to quantify the damage state. The multiaxial ductility of the material that is required to determine the damage state is estimated using triaxiality-ductility Cock and Ashby relation. Further reduction of the ductility due to the different creep mechanisms over a short and long time is also accounted for in the prediction. To simulate the different material conditions: ex-service and as-received material, different creep coefficients (A) have been assigned in the numerical modelling. In the case of ex-service material, using mean best fit data of minimum creep strain rate gives a good life prediction, while for new material, the lower bound creep coefficient should be employed to yield a comparable result with experimental data. It is also notable that ex-service material deforms faster than as-received material at the same stress level. Moreover, higher acuity provokes damage to concentrate on the small area around the notch, which initiates higher rupture life expectancy. It also found out that, the stress triaxiality and the equivalent creep strain influence the location of damage initiation around the notch area.